Morphometric, Meristic and Growth Patterns of Pangasius polyuranodon Bleeker, 1852 from the Sail River and Kampar Kiri River, Riau - Hestinar Malau; Windarti Windarti; Eddiwan Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Pangasius polyuranodon  is a type of freshwater fish that inhabit the Sail River that is polluted and Kampar Kiri River that has relatively good water quality. The difference in water conditions may affects the fish condition in general. To understand the morphometric and meristic and growth patterns ofP. polyuranodon, a research had been conducted from February- March 2018.There were 119 fishes (50 fishesfrom the Sail River and 69 fishes from Kampar Kiri River).There were 28 morphological characteristics measuredand 5 meristical characteristics counted. In the Sail fish, the formula of the fin raysis D.II.5-8, P.I-II.4-15, V.6-9, A.30-40, C.29-40, while that of the Kampar Kiri River is D.II.6-8, P.I-II.4-15, V.7-9, A.35-40, C.29-40. There were 7 morphometrical characteristic differences between male and female in the Sail River, namely body width, the distance of the anal fin to the base caudal fin, anal fin height, ventral fin height, caudal fin height, the base lenghth of adipose fin and the distance of adipose fin to the base caudal fin while that of the Kampar Kiri River is 6 morphometrical characteristic differences namely body width, eye diameter, the distance of the ventral fin to the base anal fin, the base lenghth of dorsal fin, the base lenghth of ventral fin and the base lenghth of adipose fin. The length-weight relationship of the fish from the Sail River is positive allometric, 3.007 in female and 3.430 in male, while that of the Kampar Kiri River is negative allometric, 2.544 in female and 2.655 in male.Keyword:Freshwater fish, morphometrical characteristic, meristical characteristics, positive allometric, negative allometric